Pengaruh Upah Minimum Provinsi, Motivasi Kerja, dan Loyalitas terhadap Kinerja Karyawan pada Perusahaan Jasa Sewa Mobil di Sulawesi Selatan - Serlin Serang; Suriyanti, Suriyanti; Akbar, Akbar (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to analyze the influence of UMP and work motivation on employee performance, with employee loyalty as a mediating variable, particularly in the car rental service sector in South Sulawesi. The research employs a quantitative approach using a survey of 222 respondents selected through purposive sampling. The collected data were analyzed using SEM-PLS techniques to examine the relationships among variables. The findings reveal that UMP and work motivation have positive and significant effects on employee loyalty and performance. Employee loyalty is also proven to mediate the influence of UMP and work motivation on performance. A combination of fair UMP policies and effective work motivation strategies results in sustainable employee loyalty, which directly impacts productivity improvement. This study recommends that organizations integrate UMP policies and motivation strategies with a holistic approach that includes rewards, training, and career development.